Color polymorphism and variation in microhabitat selection: a defensive strategy in males of Boana pulchella (Anura: Hylidae)? - Lermen, Luísa Nunes; Furtado, Raíssa; Hartz, Sandra Maria (Acta Scientiarum. Biological Sciences, 2022)
Anurans vary in body coloration and frequently exhibit color polymorphism, with selection by predation pressure favoring more cryptic animals. Spatial differentiation may also favor color polymorphism in some species, since cryptic morphotypes can use substrates that better match their coloration. Boana pulchella is a polymorphic species with green and brown morphotypes, but its polymorphism remains poorly understood. The aim of the present study was to determine the functionality of color polymorphism in B. pulchella as a defense strategy. Artificial green and brown clay models were placed in environments with green and brown background to determine if the two morphotypes of B. pulchella experience different frequencies of attacks. We expected that more conspicuous morphs are attacked more frequently. The attack rate, which suggests predation intent, on the models was 9.57%. The marks observed in the artificial models were left by both mammals and birds. The number of damaged models did not significantly differ between the different background environments. The results indicate that B. pulchella morphotypes are equally cryptic to predators in the studied environments. In conclusion, probably color polymorphism in B. pulchella is not operating as a defensive strategy, and other selective forces may be acting in the maintenance of color polymorphism in this species.